A word from the editors - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The editors of ICT Update congratulate CTA on its 20th anniversary. This special issue is different from the regular ICT Update in that it focuses on the forward-looking theme Mainstreaming ICTs, digital futures in ACP agriculture. Th